Bilirubin Levels as Potential Indicators of Disease Severity in Coronavirus Disease Patients: A Retrospective Cohort Study - Liu, Zeming; Li, Jinpeng; Long, Wei; Zeng, Wen; Gao, Rongfen; Zeng, Guang; Chen, Danyang; Wang, Shipei; Li, Qianqian; Hu, Di; Guo, Liang; Li, Zhengwei; et al. (Frontiers in Medicine, 2020)
Objectives: The coronavirus disease (COVID-19) pandemic has caused a large number of deaths. Some patients with severe or critical COVID-19 have been observed to have elevated bilirubin levels. Studies on the association of bilirubin level and mortality in patients with COVID-19 are limited. This study aimed to examine the role of bilirubin levels in COVID-19 severity and mortality. Methods: A retrospective cohort study was conducted in patients hospitalized with COVID-19 in Leishenshan Hospital in Wuhan, China. Cox regression analyses and logistic regression analyses were conducted to investigate the risks for mortality and disease severity, respectively. Kaplan–Meier analyses with log-rank tests were performed to assess the association between bilirubin level and survival. Results: In total, 1788 patients with COVID-19 were included in the analysis. 5.8% (4/69) of patients in the elevated serum total bilirubin (STB) group died, compared to 0.6% (11/1719) of patients in the non-elevated STB group. The median alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activities in the elevated STB group were 29 U/L (interquartile range [IQR]: 16–45 U/L ) and 22 U/L (IQR: 13–37 U /L), respectively, which were significantly higher than the median ALT (median: 23, IQR: 15–37) and AST (median: 20, IQR: 16–26) activities in the non-elevated STB group (both p<0.05). Patients with an elevated STB level showed increased mortality (hazard ratio [HR]: 9.45, P=0.002), elevated conjugated bilirubin (CB) levels (HR: 4.38, P=0.03), and an elevated ratio of CB to unconjugated bilirubin (UCB, CB/UCB) (HR: 2.49, P=0.01). CB/UCB was positively correlated with disease severity (odds ratio: 2.21, P=0.01). Conclusions: COVID-19 patients with elevated STB and CB levels had a higher mortality, and CB/UCB was predictive of disease severity and mortality. Thus, it is necessary to pay special attention to COVID-19 patients with elevated bilirubin levels in clinical management.